Stool Xpert® MTB/RIF Ultra for TB diagnosis in children: experience from a national scale-up programme - S. Kabir; S. Choudhury; T. Rahman; S.M.M. Rahman; M.K.M. Uddin; A. Nashra; A. Hossain; S. Naher; K.M.S. Towhid; L. Shahrin; S. Ahmed; P. Daru; et al. (IJTLD Open)
INTRODUCTION: We describe the programmatic scale-up of stool testing using Xpert® MTB/RIF Ultra (Ultra), as recommended by the WHO to improve childhood pulmonary TB (PTB) diagnosis. METHODS: USAID's Alliance for Combating TB in Bangladesh Activity, in collaboration with the National TB Control Programme, is implementing a stool-based diagnostic approach at 51 healthcare facilities in Bangladesh to improve PTB detection. Specimens from children (<15 years) with presumptive TB were tested using ‘stool Ultra’ with routine TB diagnostics. Physicians confirmed TB diagnosis and provided treatment as per national guidelines. RESULTS: Between March 2022 and December 2023, 16,429 specimens were tested, 871 (5.3%) were positive, and 642 (73.7%) showed ‘trace detected’ results. Positivity was significantly higher among females, and children presented with ‘only cough ≥2 weeks’, ‘cough ≥2 weeks + weight loss’, or ‘fever ≥2 weeks, weight loss, fatigue + contact history’. Positivity was higher among ‘10–14 years old’ children; however, ‘trace detected’ was highest among ‘5–9 years’, followed by children aged ‘>2–<5 years’ and ‘0–2 years’. CONCLUSIONS: Testing stools using Ultra provides a more effective way of diagnosing bacteriologically positive PTB in children. However, positivity varies with presenting symptoms/criteria, highlighting the need for careful diagnostic evaluation to ensure optimum use of limited diagnostic resources.